Emprego do óleo de Borago officinalis L. no desenvolvimento de formulações semissólidas e nanocápsulas poliméricas destinadas ao tratamento tópico de doenças inflamatórias da pele - Schiavo, Julia Weber (2014)
This study aimed to obtain semisolids formulations and lipid core nanocapsules containing borage oil associated or not with betamethasone dipropionate, for their application in the treatment of atopic dermatitis. A gel-cream containing borage oil was prepared and presented satisfactory results for performed tests (pH, spreadability and viscosity suitable for topical application). The in vivo assay showed topical anti-inflammatory action of the oil in rats. Additionally, nanocapsule suspensions containing borage oil and betamethasone dipropionate were prepared by interfacial deposition of preformed polymer method and were characterized. The colloidal suspensions, showed a slightly acid pH (6.0-6.2), nanosized particles (180-210 nm), with a low polydispersity index (<0.1), negative zeta potential (-9 to -16 mV), betamethasone content was close to theoretical and encapsulation efficiency of approximately 100%. After 15 days of storage at room temperature, only zeta potential. Photodegradation study of of betamethasone dipropionate using UVC light was performed. It was observed a protection against photodegradation conferred by the nanostructured drug delivery systems. The in vitro release study of betamethasone dipropionate from nanocapsule suspensions demonstrated the ability of nanostructures to decrease the drug release. These nanostructures were incorporated into hydrogels (Carbopol® Ultrez and Cellosize®). The hydrogels were evaluated and showed acidic pH, nanosized particle, betamethasone content near to theoretical (0.5 mg / g) and pseudoplastic behavior (Herschel-Bulkley model). In vitro release study of betamethasone dipropionate from the hydrogels demonstrated a reduced release of the drug in the different analysis times, as compared with hydrogels containing the non-associated drug. The in vivo anti-inflammatory assay showed the anti-inflammatory activity of the hydrogels containing the nanostructures, which can demonstrate the drug and the oil activity when combined with polymeric nanocapsules.